PENGARUH KESADARAN LINGKUNGAN (GREEN AWERENES) AKAN KEPUTUSAN PEMBELIAN KONSUMEN: LITERATURE REVIEW - Ahmadi, Mirzam Arqy (Journal Financial, Business and Economics, 2024)
Environmental change is currently a very important issue and is being paid attention to by the government. The impact caused by environmental damage will be very detrimental to society and business people. Currently, people are aware of the impact of environmental changes that are occurring, one of which is the uncertain climate change in Indonesia. This makes business people create various ideas to support environmental awareness, such as making products with environmentally friendly materials or using environmentally friendly packaging. The creation of environmentally friendly product ideas influences consumer behavior in making decisions to purchase a product. Consumers who are aware of green awareness will consider and choose environmentally friendly products. This research discusses the influence of green awareness on consumer purchasing decisions. In this research, education is an important factor in building community environmental awareness